2012
DOI: 10.1007/s40003-012-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Vegetable Wastes for Bioenergy Generation

Abstract: Vegetable wastes occur throughout the supply chain and vary widely depending on its processing. Globally, more than 30 % of the loss occurs at the retail and consumer levels, of which the post-harvest and processing level wastages account for the major share. The wastes so generated pose an environmental threat and call for the development of a pollution-free model. Studies on the characterization of unutilized, rotten, and discarded fractions of the vegetable wastes indicate their potential candidature for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 83 publications
(37 reference statements)
0
33
2
Order By: Relevance
“…This waste can be fed to livestock, applied to agricultural fields as fertilizer, or dumped in landfills (Charmley et al, 2006;Nelson, 2010). During the past decade there has been increasing global interest in using these wastes for bioenergy generation (Kryvoruchko et al, 2009;Arapoglu et al, 2010;Singh et al, 2012;Wang, 2013). In June of 2009, Cavendish Farms © opened a facility to convert solid potato processing wastes to biomethane gas via an anaerobic digestion process at its plant in New Annan, Prince Edward Island (http://www.cavendishfarms.com/uploadedFiles/Grocery Products/Canada/About Us/Sustainability/Fact-Technical%20 sheet v6.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…This waste can be fed to livestock, applied to agricultural fields as fertilizer, or dumped in landfills (Charmley et al, 2006;Nelson, 2010). During the past decade there has been increasing global interest in using these wastes for bioenergy generation (Kryvoruchko et al, 2009;Arapoglu et al, 2010;Singh et al, 2012;Wang, 2013). In June of 2009, Cavendish Farms © opened a facility to convert solid potato processing wastes to biomethane gas via an anaerobic digestion process at its plant in New Annan, Prince Edward Island (http://www.cavendishfarms.com/uploadedFiles/Grocery Products/Canada/About Us/Sustainability/Fact-Technical%20 sheet v6.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…The production of biofuels, such as ethanol and biodiesel (Singh et al, 2012), or the use as adsorbents for the removal of pollutants from wastewater (Lavecchia et al, 2010) are some of the proposed applications. Another promising, but still relatively unexplored, approach is the use of vegetable wastes as a raw material for the recovery of functional or healthpromoting compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fruits and vegetable waste for production of organic acid and vital enzymes has been widely reported [30]. Due to its high and easily degradable organic content, vegetable wastes show a great potential for energy bioconversion, particularly in biofuel production [57]. Crustacean by-products, generated in industrial seafood processing, have been reported in the production of chitinase and chitosanase with a wide range of applications in biomedical, food and agrochemical sectors [58,59].…”
Section: Introductionmentioning
confidence: 99%